The school counsellors about participation of pupils with learning difficulties - Kodele, Tadeja (Sodobna pedagogika, 2023)
The article is based on the assumption that, given the commitment to the Convention on the Rights of the Child (1989) and the Salamanca Declaration (1994), pupil participation in school should indeed be present in all processes that take place on a daily basis. Because many pupils face major or minor learning difficulties during their time at school, the issue of participation in solving these problems is critical, especially when a pupil has learning difficulties. In a representative sample of school counsellors from Slovenian primary schools, a combined quantitative–qualitative survey revealed that pupils’ participation in most processes or activities in school is present in just over two-fifths of schools (44%), although the majority of school counsellors (90.9%) believe that pupils’ participation in planning and providing learning assistance to pupils with learning difficulties is crucial. The qualitative analysis showed that the notion of participation is very modest and often tautological, and most counsellors see obstacles to the implementation of participation mainly among pupils, but also among school staff and management. In further research on pupil participation, it would be good to consider the perspective of pupils with learning difficulties and include more qualitative and quantitative research techniques.
Keywords: child participation; inclusion; inkluzija; obstacles; osnovna šola; ovire za participacijo; participacija otrok; pupils with learning difficulties; school counselling; school management; šolsko svetovalno delo; učenci z učnimi težavami; učne težave; vodstvo šole